Nanodomain Clustering of the Plant Protein Remorin by Solid-State NMR - Legrand, Anthony; Martinez, Denis; Grélard, Axelle; Berbon, Melanie; Morvan, Estelle; Tawani, Arpita; Loquet, Antoine; Mongrand, Sébastien; Habenstein, Birgit (Frontiers in Molecular Biosciences, 2019)
Nanodomains are dynamic membrane subcompartments, enriched in specific lipid and protein components that act as functional platforms to manage an abundance of cellular processes. The remorin protein of plants is a well-established nanodomain marker and widely serves as a paradigm to study nanodomain clustering. Located at the inner leaflet of the plasma membrane, remorins perform essential functions during signalling. Using deuterium and phosphorus solid-state NMR, we inquire on the molecular determinants of the lipid-protein and protein-protein interactions driving nanodomain clustering. By monitoring thermotropism properties, lipid acyl chain order and membrane thickness, we report the effects of phosphoinositides and sterols on the interaction of various remorin peptides and protein constructs with the membrane. We probed several critical residues involved in this interaction and the involvement of the coiled-coil homo-oligomerisation domain into the formation of remorin nanodomains. We trace the essential role of the pH in nanodomain clustering based on anionic lipids such as phosphoinositides. Our results reveal a complex interplay between specific remorin residues and domains, the environmental pH and their resulting effects on the lipid dynamics for phosphoinositide-enriched membranes.